2017
DOI: 10.1177/1056492617715323
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts of Interest as Corrupting the Checks and Balances in the Postpublication Oversight of Academic Business Journals

Abstract: In this case-based essay, we explore how conflicts of interest can corrupt the postpublication oversight process in academic business journals. We build on Carson’s comprehensive definition of the conflict of interest construct by arguing that it is, in a practical sense, not isolated and dyadic but instead is multirelational to the point of being viral. Specifically, we argue that conflicts of interest produce further conflicts of interest; this occurs at any oversight level that is tasked with investigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Conflicts may arise when individual goals or interests conflict with the goals of the organization (Arend, 2019).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Conflicts may arise when individual goals or interests conflict with the goals of the organization (Arend, 2019).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In universities, there is immense pressure from management to achieve high profiles in notable journals coupled with ineffective editorial vigilance has been conducive to fraud, and sadly most of the fraud cases are detected by whistleblowers and Ph.D. students (Gross, 2016). Arend (2017) also showed that journals often fail to follow up with the complaints and remarks that are sent, so corruption remains persistent as there is little chance of actual exposure. While it is easy to simply heap the blame on the researcher, some researchers claim that this pressure exerted will hinder the ability to even recognize that is being done is immoral or unethical in the first place (Jones & Ryan, 1998).…”
Section: Scientific Misconductmentioning
confidence: 99%
“…In post-publication peer review (PPPR), or simply post-publication analysis, including by members of the public (The Lancet 2020 ), individual or collective conscience drives individual academics or groups to seek ways to create a more “perfect” literature that is as free of error as possible, via the discovery and correction of those errors (Teixeira da Silva 2015a ; Arend 2019 ). Some of those discoveries may lead to retractions (Andersen and Wray 2019 ).…”
Section: Error Misconduct and Post-publication Peer Reviewmentioning
confidence: 99%